“Em busca de um patrocínio”: uma análise sobre o produto “relacionamentos sugar” em mídias digitais brasileiras - Barbosa, Bruno Henrique Benichio Alves (2024)
Relationships that combine financial support and affective exchange have been extensively studied in national and international research on sexual economies. With the popularization of digital media in Brazil over the last decade, this relationship model has spread through online dating services that use terms such as “sugar relationships”, “sugar daddies” and “sugar babies” to refer to a type of affective-sexual engagement in which wealthy men provide financial support to women. Drawing on theoretical frameworks from gender and sexuality studies and on methodological approaches used in ethnographies in digital contexts, this study interviewed nine sugar babies, analyzed advertisements from two sugar dating websites and one hundred female profiles registered on these sites, as well as the content of two digital influencers engaged in the sugar theme. In this vein, the research: I) Mapped the profiles of the women interviewed and those registered on two sugar dating websites from an intersectional perspective and reflected on their experiences in these engagements in terms of intertwined inequalities of class, gender, race, age, body, and region; II) Examined the meanings they insert into the ideal sugar baby model conveyed by the websites; III) Explored their purposes for seeking these relationships; and IV) Analyzed the business model of these platforms. Overall, the research sheds light on an emerging segment of commercial exploration in the line of dating websites and applications that circumvent unequal scenarios through ideals of entrepreneurship and female empowerment. In this sense, it can contribute to future research on sexual economies, power relations, and their processes of platformization and mediatization in line with neoliberalism.